IMPLEMENTASI KEGIATAN IMTAQ SEBAGAI UPAYA PENGUATAN KARAKTER RELIGIUS DAN TANGGUNG JAWAB MURID DI SD NEGERI 6 SELONG - Faizah; Arif Rahman, Hakim; Baiq, Abidaturrosida; Silvi Diah Ayu Nurkumala , Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of IMTAQ activities as an effort to strengthen students' religious character and responsibility at SD Negeri 6 Selong. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings revealed that IMTAQ activities are conducted regularly every Friday through collective prayers, recitation of Surah Yasin, singing Islamic songs, and performing Dhuha prayer. The implementation of these activities contributes to strengthening students' religious character and sense of responsibility through discipline and adherence to school regulations. The success of the program is supported by the school's commitment, active teacher involvement, and student participation, although several challenges remain, including some students' lack of focus and limited implementation time. Therefore, IMTAQ activities serve as an effective program for strengthening students' religious character and responsibility at SD Negeri 6 Selong.